Rapid monitoring of health services utilization following a shift in coverage from brand name to biosimilar drugs in British Columbia—An interim report. Issue 7 (28th May 2020) - Fisher, Anat; Kim, Jason D.; Dormuth, Colin R.
Abstract: Purpose: We explored changes in health services utilization associated with the Biosimilars Initiative introduced in British Columbia on May 27, 2019. To maintain drug coverage, the policy requires users of originator infliximab or etanercept to transition to biosimilar versions. We present a three‐month interim analysis of this initiative. Methods: We conducted a rapid monitoring analysis to evaluate changes in health services utilization three months after the policy was introduced compared with a three‐year period before the policy's introduction. Using the administrative claims data of the British Columbia Ministry of Health, we assembled three historical cohorts and one policy cohort of users of each originator drug (8 cohorts in total). Cumulative incidences of medication refills, switching, and visits to physicians were the outcome measures used to compare policy and historical cohorts. Likelihood ratios were used to quantify statistical differences between each policy cohort and its respective historical controls. Likelihood ratios above 7.1 were considered statistically significant. Results: The four infliximab cohorts included 436 patients on average, mean age 56 to 59, 53% to 55% females. The four etanercept cohorts included 1826 patients on average, mean age 57 to 58, 60% to 63% females. Three months after the policy's introduction, 21% of patients treated in the policy cohorts transitioned to the biosimilar versions. Health services utilization in the policy cohorts were consistent with the historical cohorts. Conclusions: An increase in visits to physicians was expected but not detected in the first three months of the Biosimilars Initiative. The impacts of the policy will continue to be monitored.